Metarhizium sp. isolated from dead Pachnoda interrupta (Coleoptera: Scarabaeidae) as a potential entomopathogenic fungus for the pest insect: proof-of-concept for autodissemination. (3rd February 2016) - Getahun, Merid N.; Biasazin, Tibebe D.; Wolde-Hawariat, Yitbarek; Bengtsson, Jonas M.; Hillbur, Ylva; Seyoum, Emiru
Abstract : Sustainable pest management requires the use of ecosystem-friendly control options (e.g. entomopathogens) coupled with target-specific application methods. Here we investigate the susceptibility of the sorghum chafer ( Pachnoda interrupta, Olivier) to Metarhizium sp., isolated from dead P. interrupta under field conditions over several years. Target-specific trapping was achieved using Japanese beetle traps or locally made autoinoculation devices, with methyl salicylate or banana as an attractant. Of the attracted and infected beetles, 49% mortality was achieved during October 2005 and 71% during July 2006, while the corresponding mortality in control treatments was 13 and 5%, respectively. We further confirmed that the mortality of the beetles was due to the fungal treatment as 50 and 80% of the dead beetles showed mycosis, respectively. The performance of the pathogen was also investigated in an autodissemination device in 2008 and 2009, where the beetles that were attracted passed through an inoculation chamber. Of the attracted and infected beetles in the autodissemination device, 58.5% (October) and 90.9% (July) were dead within 15 days after treatment. Control mortality was only 3 and 2%, respectively. The potential for horizontal transmission was investigated, where 47% (October) and 59% (July) of the beetles exposed to the pathogen through horizontal transmission were killed. The pathogen was found to be viable for more than 3 days in the field. Our results show that Metarhizium sp. has potential as a biological control agent, and for achieving autodissemination using the target pest as the vector.